The Influence of the Work Environment on Employee Work Discipline at the Central Statistics Agency Office, Gowa Regency - Fadhilah Rezkiyanti; Risma Niswaty; Isgunandar Isgunandar (ASHA Publishing, 2025)
Human resources are essential to the success of an organization and play a vital role in any agency or institution.